Stroking parameters in top level swimmers with a disability - Pelayo, P.; Sidney, M.; Moretto, P.; Wille, F.; Chollet, D. (Medicine & Science in Sports & Exercise, 1999)
Purpose: The purposes of this study were to analyze velocity (V), stroke length (SL), and stroke rate (SR) values during the 100-m freestyle competitive events in top level male and female swimmers with a disability (DS) according to the international Functional Classification System (FCS) and to compare the results obtained with those of able-bodied swimmers (ABS). Methods: DS (N = 119) and ABS (N = 32) were tested in real competitive conditions during European and French swimming championships in the A finals of the 100-m freestyle. Results: V and SL increased significantly (P < 0.01) according to the level of ability from class S3 up to S10. SL values were significantly different (P < 0.01) between males and females in each class group. On the contrary, SR was not significantly different between genders, between each class group of FCS, and also with ABS. The major result of this study was that stroke length was related to velocity whereas stroke rate was not. The differences in weekly training time between each class of DS were not significantly different and showed that performances seemed to be more related to the various locomotor disabilities than to the training status. Conclusions: These findings, which are discussed, showed that stroke index (SI = V.SL) could be used as a sensitive criterion to assess the swimmer with a disability in relationship to his classification level.